The impact of social media on the personal financial management behavior of young people in Hanoi, Vietnam - Huong, Ngo Thi Thu; Ha, Luong Thanh; Tram, Do Ngoc; Huong, Nguyen Thi Mai; Huong, Tran Quynh (Edelweiss Applied Science and Technology, 2026)
In the digital era, social media has become a key channel for accessing financial information, particularly among Generation Z (Gen Z). Beyond communication, it serves as an important source of financial knowledge and influences decision-making. However, empirical evidence on its impact in developing countries, including Vietnam, remains limited. This study examines the effect of social media on the personal financial management behavior of Gen Z in Hanoi, focusing on financial attitude, subjective financial knowledge, and financial socialization. A mixed-method approach was adopted, with data collected from 258 respondents and analyzed using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that social media use and subjective financial knowledge significantly influence financial behavior, while financial attitude has a weaker effect, and financial socialization mainly exerts an indirect influence. These findings highlight the role of social media as an informal learning channel and its potential to enhance financial literacy and promote responsible financial practices among Gen Z.